1995
DOI: 10.1149/1.2050025
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Activation and Recrystallization of B+‐ and  BF 2  +  ‐ Implanted LPCVD Amorphous‐Si Films

Abstract: Low‐temperature (600°C) activation and recrystallization of the low‐pressure chemical vapor deposition (LPCVD) amorphous‐Si films B+‐ and BF2+‐normalImplanted with different implantation dosages and projection ranges have been investigated. The boron dopant in the amorphous‐Si layer can enhance the recrystallization, resulting in the shorter incubation time and smaller grain size then the undoped specimens. For the BF2+‐normalImplanted specimens, the existence of fluorine atoms could postpone the grain nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The crystallization phenomenon is expected to greatly influence the redistribution of the dopants, and may lead to unusual variation of their concentration profiles versus the annealing time. For instance, it has been shown that both the nature of the dopant and its concentration can influence the silicon crystallization [9][10]. Furthermore, dopant diffusion depends on the crystalline state of the Si matrix, being faster in polycrystalline and amorphous Si than in monocrystalline Si.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization phenomenon is expected to greatly influence the redistribution of the dopants, and may lead to unusual variation of their concentration profiles versus the annealing time. For instance, it has been shown that both the nature of the dopant and its concentration can influence the silicon crystallization [9][10]. Furthermore, dopant diffusion depends on the crystalline state of the Si matrix, being faster in polycrystalline and amorphous Si than in monocrystalline Si.…”
Section: Introductionmentioning
confidence: 99%